Optimal collective reputation - Pu-yan Nie; Hong-Xing Wen; Chan Wang (Journal of Applied Economics, 2023)
Collective reputation, such as watches "made in Switzerland", affects the whole industry all over the world. This article highlights the relationship between competition and collective reputation. First, collective quality level depends on firms objectives. Second, the collectively determined quality of profit incentive firms reaches social optimal level. Finally, quality restriction is more efficient than subsidies to promote collective quality. The policy implication is that antitrust policy should not care about jointly determined quality for profit incentive firms. Further, cooperative innovation is encouraged to promote the collective reputation or cooperative innovation promotes the values of patents by collective reputation.
Keywords: 330; antitrust; Collective reputation; competition; social welfare